A multicriteria analysis of the community initiative INTERREG II Spain-Morocco (1994-1999) - Andres J. Marchante; Bienvenido Ortega; Jose Lopez (European Regional Science Association (ERSA), 2002)
The aim of this paper is to analyse the projects within the Community Initiative Interreg II Spain-Morocco (1994-1999) designed to develop cross-border cooperation. This work does not attempt a full evaluation of the programme.It is a preliminary study necessary to develop a final evaluation from a "bottom-up" perspective. Accordingly, its contribution to the analytical agenda of the evaluation consists of reconstituting the logic of the programme by classifying the projects in terms of three main criteria: degree of financial execution, contribution to the production of expected impacts and "synergy" with another programmes. The conceptual basis of the work has been the Multicriteria Analysis methodology recommended by the European Commission's framework MEANS.
Keywords: 330